Efficient Spin‐to‐Charge Interconversion in Weyl Semimetal TaP at Room Temperature. Issue 36 (5th December 2022) - Mendes, Joaquim B. S.; Vieira, Andriele S.; Cunha, Rafael O.; Ferreira, Sukarno O.; dos Reis, Ricardo D.; Schmidt, Marcus; Nicklas, Michael; Rezende, Sergio M.; Azevedo, Antonio
Abstract: In this paper, spin‐to‐charge current conversion properties in the Weyl semimetal TaP by means of the inverse Rashba–Edelstein effect (IREE) with the interfacial integration of this quantum material with the ferromagnetic metal Permalloy (Py = Ni81 Fe19 ) are presented. The spin currents are generated in the Py layer by the spin pumping effect (SPE) from microwave‐driven ferromagnetic resonance and are detected by a dc voltage along the TaP crystal, at room temperature. A field‐symmetric voltage signal is observed without the contamination of asymmetrical lines due to spin rectification effects observed in studies using metallic ferromagnets. The observed voltage is attributed to spin‐to‐charge current conversion based on the IREE, made possible by the spin–orbit coupling induced intrinsically by the bulk band structure of Weyl semimetals. The measured IREE coefficient λIREE = (0.30 ± 0.01) nm is two orders of magnitude larger than in graphene and is comparable to or larger than the values reported for some metallic interfaces and for several topological insulators. Abstract : The spin‐to‐charge current conversion properties in topological Weyl semimetal TaP are investigated by spin pumping effect experiments. The spin‐to‐charge current conversion is attributed to the inverse Rashba–Edelstein effect occurring at the TaP/ferromagnet interface. In addition, it is verified that the TaP is much more efficient to convert spin current into charge current than other topological materials.